Pengaruh Current Ratio(CR), Debt to Equity Ratio(DER) dan Total Asset Turnover(TATO) Terhadap Return on Equity(ROE) Pada Perusahaan Property yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023 - Putri Juliana (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to test the effect of Firm size, Current Ratio (CR), Debt to equity ratio (DER) on Cash Turnover ratio (CTO) on textile and garment sector companies listed on the Indonesian stock exchange during 2020-2023. This research method uses multiple linear regression analysis with data management using the STATA 17 program. The sampling method in this study uses the purposive sampling technique. The results of the F test showed simultaneously Firm size, Current Ratio (CR), Debt to equity (DER), Total asset Turnover (TATO) is significant to Return on Equity (ROE). Partial T test results, Firm Size and Current Ratio (CR) affect Total Asset Turnover (TATO). On the other hand, Debt to equity ratio (DER) has no effect on Total Asset Turnover (TATO).